From eyes’ microtremors to critical flicker fusion - Pedro Lencastre; Rujeena Mathema; Pedro G. Lind (PLoS ONE, 2025)
The critical flicker fusion threshold (CFFT) is the frequency at which a flickering light source becomes indistinguishable from continuous light. The CFFT is an important biomarker of health conditions, such as Alzheimer’s disease and epilepsy, and is affected by factors as diverse as fatigue, drug consumption, and oxygen pressure, which make CFFT individual- and context-specific. Other causal factors beyond such biophysical processes are still to be uncovered. We investigate the connection between CFFT and specific eye-movements, called microtremors, which are small oscillatory gaze movements during fixation periods. We present evidence that individual differences in CFFT can be accounted by microtremors, and design an experiment, using a high-frequency monitor and recording the participant’s eye-movements with an eye-tracker device, which enables to measure the range of frequencies of a specific individual’s CFFT. Additionally, we introduce a classifier that can predict if the CFFT of specific participant lies in the range of high or low frequencies, based on the corresponding range of frequencies of eyes’ microtremors. Our results show an accuracy of 85% for a frequency threshold of 60 Hz and 88% for a threshold of 120 Hz.